Early Marriages Last Longer: Pre-electoral Coalitions and Government Survival in Europe. Issue 2 (27th May 2014) - Chiru, Mihail
Abstract : While the existence of pre-electoral coalitions fundamentally modifies the bargaining environment in which potential cabinet formulas are negotiated, the survival chances of cabinets that include them follow predictable yet different patterns to those of 'regular' coalition governments. This article combines original and existing data sets on Western and Central and Eastern European cabinets with information about pre-electoral coalitions (1944–2008) in order to estimate the impact of such alliances on government survival rates. In doing so, I employ a Cox Proportional Hazard model and a 'competing risks' research design which distinguishes between replacement and early election hazards. The findings indicate that both Western and post-communist cabinets formed by pre-electoral coalitions exhibit considerably lower rates of discretionary terminations. This effect is reversed in the case of incumbent pre-electoral coalitions. Last but not least, Western European cabinets that replicate pre-electoral coalitions are significantly less likely to end through dissolution and early elections.